PENGARUH PENGAWASAN PIMPINAN, KEPATUHAN SOP DAN LINGKUNGAN KERJA TERHADAP KESELAMATAN KERJA KARYAWAN DENGAN DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING DI PERKEBUNAN KELAPA SAWIT PT. AGRO ANDALAN KABUPATEN SEKADAU PROVINSI KALIMANTAN BARAT - Dadam Saeful Bahri; Liswandi Liswandi; Yahya Agung Kuntadi (POLITEKNIK LP3I JAKARTA, 2022)
This study aims to analyze the effect of leadership supervision, SOP compliance and work environment on employee safety with work discipline as an intervening variable. The independent variables of this research are leadership supervision, SOP compliance, and work environment. The intervening variable is work discipline and the dependent variable is work safety. The data used in this study were sourced from the perceptions of employees of PT. Mainstay Agro. The sampling technique used in this research is using random sampling method. To determine the sample size, the Solvin formula is used and so that the obtained sample size of 205 employees. To answer the research objectives, an analytical method is used, namely SEM PLS. The results of the study showed that leadership supervision, SOP compliance, work environment, and work discipline had a significant effect on work safety. In addition, this study also proves that leadership supervision, SOP compliance, and work environment have a significant effect on work discipline, so that the indirect effect test concludes that work discipline is able to mediate the influence of leadership supervision, SOP compliance, and work environment on work safety.Key words: Leadership Supervision, SOP Compliance, Work Environment, Work Discipline, Employee Safety